Biology and biometry of the Atlantic bumper, Chloroscombrus chrysurus (Linnaeus, 1766) (Teleostei: Carangidae), off Fortaleza county, Ceará State, Brazil - Cunha, Francisca Edna de Andrade; de Freitas, João Eduardo Pereira; Feitosa, Caroline Vieira; Monteiro-Neto, Cassiano (Arquivos de Ciências do Mar, 2017)
The Atlantic bumper, Chloroscombrus crysurus, a demersal fish fairly common in coastal waters, is one of the five most abundant species caught by beach seines at Fortaleza county, Ceará State, Brazil. The present paper analyses the seasonal abundance, the total lengh frequency distribution, as well as food habits and biometry of that species. Forty beach seine hauls were monitored from May, 1991 to April, 1992. Largest and smallest catches occurred, respectively in the bimesters July-August and January-February. The species seasonal abundance varied similarly to the rainfall seasonal trend. Nearly all individuals caught were juveniles or imature at sizes ranging from 30 to170 mm total length. The juvenile recruitment occurred in May-June. The studied meristic and morphometric relationships were within the standard ones described by other autors for this species. The diet of the Atlantic bumper includes food items such as crustaceans, mollusk grubs, fishes and seaweed.